Management of multiple neurological complications in mixed connective tissue disease: A case report. Issue 31 (August 2018) - Hao, Yulei; Feng, Liangshu; Teng, Yongliang; Cheng, Yingying; Feng, Jiachun
Abstract: Rationale: Mixed connective tissue disease (MCTD) refers to an overlapping condition of different autoimmune disorders such as systemic lupus erythematosus, cutaneous systemic sclerosis, rheumatoid arthritis, polymyositis, and dermatomyositis. However, MCTD manifesting as transverse myelitis is extremely rare. Herein, we report a case of MCTD with both central and peripheral nervous system involvement. Patient concerns: We describe and discuss the clinical findings and management of a 36-year-old man presented with a 2-week history of sudden bilateral lower-limb paralysis and dysuresia. Further investigation of his medical history showed a 6-month history of autoimmune symptoms. Diagnoses: The patient was diagnosed with MCTD, transverse myelitis, mononeuritis multiplex, and multiple lacunar infarctions. Interventions: A combination of low-dose methylprednisolone (40 mg/d) and hydroxychloroquine sulfate (400 mg/d) was administered. Outcomes: After treatment, the symptoms were significantly improved. The patient recovered well after 1 year follow-up and the sequela was urinary incontinence and grade 4/5 lower-extremity muscle strength. Lessons: MCTD with multiple neurological complications is extremely rare and poses diagnostic and therapeutic challenges. Our experience suggests a combination of low-dose corticosteroids and hydroxychloroquine sulfate may be an effective therapeutic approach.